034 Early cardiovascular dysfunction drives in-hospital trauma mortality. Issue 12 (21st November 2019) - Carden, Rich; Lockey, David; Brohi, Karim
Abstract : Background: Improvements in trauma resuscitation practice have reduced the early in-hospital mortality from haemorrhage and its immediate sequelae. Early cardiovascular dysfunction (CVD) is a poorly understood and under-recognised major contributor to contemporary trauma deaths. The objective of this study was to demonstrate the prevalence and impact of CVD in a population of trauma patients without catastrophic TBI. A review of data collected prospectively at a UK Major Trauma Centre from 2008–2018. Adult trauma patients over the age of 15 were included. CVD was defined as a score of 4 on admission or day 1 of admission using the cardiovascular component of the SOFA score. 1042 patients were included, of which 125 (12%) had CVD. The 28-day mortality rate in the total population was 4.8%, and of those 64% had CVD. CVD was associated with a blunt mechanism of injury (81.6%), male gender (81.6%), and a high injury severity score (median=27). In the CVD group the major haemorrhage protocol was activated in 76.8% of patients, and 73.6% received more than 4 units of red blood cells in the first 24 hours. Early CVD was more prevalent than any other single-system dysfunction assessed with the SOFA. All deaths with single organ failure in a SOFA domain other than cardiovascular had concurrent CVD. In predicting 28-day mortality, CVD had an AUROC of .882 (CI=0.810–0.955, p =0.000), odds ratio of 57.2, and sensitivity and specificity of 86.7% and 89.7% respectively. Multiple regression analysis identified admission base deficit, admission systolic blood pressure and heart rate, increased age, blunt mechanism, increased injury severity score, and 24-hour crystalloid administration as strong predictors of developing CVD. CVD is the contemporary driver of in-hospital non-head injured trauma mortality. The resuscitation phase is the window of opportunity for discovery of novel treatments.